Snow falling on cedars (Universal City, CA : Universal Studios, 2000)
A murder trial has upset the quiet community of San Piedro, and now this tranquil village has become the center of controversy. For a local reporter the trial strikes home when he finds his ex-lover is linked to the case.
Videodisc release of the 1999 motion picture.
Based on the novel by David Guterson.
Music by James Newton Howard ; screenplay by Ron Bass and Scott Hicks ; directed by Scott Hicks.
Ethan Hawke, James Cromwell, Richard Jenkins, Youki Kudoh, James Rebhorn, Sam Shepard, Rick Yune, Max von Sydow.
PG-13.
DVD format.
Keywords: Films for the hearing impaired; Japanese Americans -- Washington (State) -- Fiction; Trials (Murder) -- Washington (State) -- Fiction; Journalists -- Washington (State) -- Fiction